Synchronization of the Mobile Robot to a Chaotic Trajectory - Rafikova, Elvira; Rafikov, Marat; Rinaldo, Guilherme (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we propose a new approach that allows a mobile robot to follow a chaotic trajectory, which is a projection of the strange attractor of any deterministic chaotic system, on the xoy plane. This approach is reminiscent of the master-slave synchronization. The desired chaotic curve is expressed in terms of a virtual reference robot. The suboptimal State Dependent Riccati Equation (SDRE) control is applied to achieve synchronization between the real and virtual robots. We demonstrate two examples of this approach, leading the robot system to a synchronization with Rossler and Lorenz strange attractor’s xoy projections.